Evaluation of the Chloride Requirement of the Broiler Breeder Hen Avaliação da Exigência de Cloro para Matrizes Pesadas - JC Harl (Brazilian Journal of Poultry Science, 2000)
Two experiments wore conducted to evaluate the chloride requirement of the broiler breeder hen. Experiments were conducted for a twelve-week period and seven experimental diets wore fed. The diets contained the following dietary chloride levels: 0. 040, 0. 047, 0. 054, 0.060, 0.073, 0.09g, and 0. 174%. Sodiam bicarbonate was used to maintain a constant level of sodium. Levels of dietary chloride below 0.054% reduced EF; EW, & EC (ED X (EW-shell wt). Also, the highest level of dietary chloride reduced all characteristics. Dietary chloride did not have a significant effect on body weight gain or fertility and hatchability of eggs. The Nationa/ Research Council (1994) suggests that the broller breeder hen have daily chloride intake of 185 milligrams per hen per day. In Experiments 1 and 2 the requirement was 96.1 mg/hen/day and 101. 1 mg/hen/day for EP, 116.1 mg/hen/day and 148.3 mg/hen/day for maximum EW, and 95.9 mg/hen/day and 109. 5 mg/hen/day for EC, respectively. Foram conduzidos dois experimentos para avaliar o requerimento de cloro para matrizes pesadas. O período experimental foi de doze semanas e foram testadas sete rações. As racões continham os seguintes níveis de cloro: 0,040, 0,047, 0,054, 0,060, 0,073, 0,099 e 1,74%. Foi utilizado o bicarbonato de sódio para se manter um nível constante de sódio. Os níveis de cloro abaixo de 0,054% reduziram a produção, o peso e o conteúdo dos ovos, o mesmo ocorrendo com o nível mais alto de cloro na ração. Os níveis de cloro não exerceram um efeito significativo sobre o peso corporal, fertilidade e eclodibilidade dos ovos. ONRC (1994) sugere um nível de 185mg de cloro por dia para matrizes pesadas. Nos experimentos 1 e 2, o requerimento encontrado foi de 96,1 mg/ave/dia e 101,1 mg/ave/dia para produção de ovos, 116,1 mg/ave/dia e 148,3 mg/ave/dia para peso máximo dos ovos e 95,9 mg/ave/dia e 109,5 mg/ave/dia para conteúdo do ovo, respectivamente.